Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine which of the numbers 1, 2, and 3 satisfy the inequality [tex]\( 2x + 1 \geq 7 \)[/tex], let's test each value step-by-step.
1. For [tex]\( x = 1 \)[/tex]:
- Substitute [tex]\( x = 1 \)[/tex] into the inequality: [tex]\( 2(1) + 1 \geq 7 \)[/tex].
- Calculate the left side: [tex]\( 2 \cdot 1 + 1 = 2 + 1 = 3 \)[/tex].
- Check the inequality: [tex]\( 3 \geq 7 \)[/tex], which is false.
2. For [tex]\( x = 2 \)[/tex]:
- Substitute [tex]\( x = 2 \)[/tex] into the inequality: [tex]\( 2(2) + 1 \geq 7 \)[/tex].
- Calculate the left side: [tex]\( 2 \cdot 2 + 1 = 4 + 1 = 5 \)[/tex].
- Check the inequality: [tex]\( 5 \geq 7 \)[/tex], which is false.
3. For [tex]\( x = 3 \)[/tex]:
- Substitute [tex]\( x = 3 \)[/tex] into the inequality: [tex]\( 2(3) + 1 \geq 7 \)[/tex].
- Calculate the left side: [tex]\( 2 \cdot 3 + 1 = 6 + 1 = 7 \)[/tex].
- Check the inequality: [tex]\( 7 \geq 7 \)[/tex], which is true.
Based on this analysis:
- [tex]\( x = 1 \)[/tex] does not satisfy the inequality [tex]\( 2x + 1 \geq 7 \)[/tex].
- [tex]\( x = 2 \)[/tex] does not satisfy the inequality [tex]\( 2x + 1 \geq 7 \)[/tex].
- [tex]\( x = 3 \)[/tex] does satisfy the inequality [tex]\( 2x + 1 \geq 7 \)[/tex].
Therefore, out of the numbers 1, 2, and 3, only 3 is a solution to the inequality [tex]\( 2x + 1 \geq 7 \)[/tex].
1. For [tex]\( x = 1 \)[/tex]:
- Substitute [tex]\( x = 1 \)[/tex] into the inequality: [tex]\( 2(1) + 1 \geq 7 \)[/tex].
- Calculate the left side: [tex]\( 2 \cdot 1 + 1 = 2 + 1 = 3 \)[/tex].
- Check the inequality: [tex]\( 3 \geq 7 \)[/tex], which is false.
2. For [tex]\( x = 2 \)[/tex]:
- Substitute [tex]\( x = 2 \)[/tex] into the inequality: [tex]\( 2(2) + 1 \geq 7 \)[/tex].
- Calculate the left side: [tex]\( 2 \cdot 2 + 1 = 4 + 1 = 5 \)[/tex].
- Check the inequality: [tex]\( 5 \geq 7 \)[/tex], which is false.
3. For [tex]\( x = 3 \)[/tex]:
- Substitute [tex]\( x = 3 \)[/tex] into the inequality: [tex]\( 2(3) + 1 \geq 7 \)[/tex].
- Calculate the left side: [tex]\( 2 \cdot 3 + 1 = 6 + 1 = 7 \)[/tex].
- Check the inequality: [tex]\( 7 \geq 7 \)[/tex], which is true.
Based on this analysis:
- [tex]\( x = 1 \)[/tex] does not satisfy the inequality [tex]\( 2x + 1 \geq 7 \)[/tex].
- [tex]\( x = 2 \)[/tex] does not satisfy the inequality [tex]\( 2x + 1 \geq 7 \)[/tex].
- [tex]\( x = 3 \)[/tex] does satisfy the inequality [tex]\( 2x + 1 \geq 7 \)[/tex].
Therefore, out of the numbers 1, 2, and 3, only 3 is a solution to the inequality [tex]\( 2x + 1 \geq 7 \)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.